Impact of the intervention program "JolinchenKids - fit and healthy in daycare" on energy balance related-behaviors: results of a cluster controlled trial - Berit Steenbock; Christoph Buck; Hajo Zeeb; Stefan Rach; Claudia R. Pischke (BMC, 2019)
Abstract Background The purpose of this study was to evaluate the multi-component health promotion program, JolinchenKids - fit and healthy in daycare, designed to promote physical activity (PA), healthy eating, and mental wellbeing among 3- to 6-year-old preschoolers. Methods For this cluster controlled trial, 62 daycare facilities (DFs) from thirteen different federal states in Germany were recruited (31 intervention, 31 control DFs). Outcome measures were children's habitual PA, fruits and vegetable consumption, consumption of unsweetened beverages and snacks with parents as raters. Study nurses assessed children's body composition and motor skills. Data was collected at baseline and 12 months later. To track adherence to the implementation of intervention modules at individual DF groups, an implementation calendar was used from baseline to follow-up. Linear mixed models were used to investigate effects for survey, group and their interaction at the individual level while accounting for clustering. Results Samples of 831 (baseline) and 641 (follow-up) children aged 4.3 ± 0.8 and 5.2 ± 0.8 years were analysed. More than half of the intervention DFs chose the nutrition or PA module for the first year of implementation while an implementation level of > 50% was only achieved in less than a third. A significant intervention effect (survey × group interaction) was found for the standing long jump favouring children at intervention DFs (β = 3.08; 95% Confidence interval [CI]: (0.09; 6.07)). No significant intervention effects were found for time spent on PA, total screen time, dietary habits, and body composition, i.e. body-mass-index and percentage of body fat. Conclusions Participation in JolinchenKids - fit and healthy in daycare led to improvements in some indicators for motor skills. However, other health outcomes and behaviours were not affected by program participation over the course of 1 year. Trial registration German Clinical Trials Register DRKS00011065 (Date of registration 16-09-2016).